STATIC AND DYNAMIC STABILITY OF GRAVI-INERTIAL SENSORS WITH CAPACITIVE DIFFERENTIAL SYSTEM OF SENSITIVITY ADJUSTMENT - I. Z. Gilavdary; S. Mekid; N. N. Riznookaya; A. Abdul Sater (Приборы и методы измерений)
The design of a gravi-inertial sensor with an elastically suspended sensing mass exhibiting a maximum sensitivity and minimum noise level is being studied. It is conceived that such a sensor contains a torsion mass-spring system, a capacitive pick-off circuit to detect motions of the sensing mass, and a capacitive system to reduce torsion stiffness. Both capacitive systems are combined into a single differential capacitance electrostatic system. The torsion stiffness is reduced by applying an electric field. Problems resulting from the electrostatic asymmetry of the differential system are studied analytically and numerically. The quasi-static and dynamic modes of the free movement of the sensing mass, in the absence of energy loss, are considered. The angular intervals of stability of the sensing mass movement in the electrostatic field, depending on the differential system asymmetry parameter and a frequency of free oscillations «proof mass», are calculated.